Behavioral reactivity to acute stress among Black and White women with type 2 diabetes: The roles of income and racial discrimination. (September 2016) - Bermudez-Millan, Angela; Schumann, Kristina P; Feinn, Richard; Tennen, Howard; Wagner, Julie
This study investigated relationships of income and self-reported racial discrimination to diabetes health behaviors following an acute stressor. A total of 77 diabetic women (51% Black, 49% White) completed a laboratory public speaking stressor. That evening, participants reported same-day eating, alcohol consumption, and medication adherence; physical activity was measured with actigraphy, and the next morning participants reported sleep quality. Measures were repeated on a counterbalanced control day. There was no mean level difference in health behaviors between stressor and control days. On stressor day, lower income predicted lower physical activity, sleep quality, and medication adherence, and higher racial discrimination predicted more eating and alcohol consumed, even after accounting confounders including race and control day behaviors.